Whole-exome sequencing in a consanguineous Pakistani family identifies a mutational hotspot in the COL7A1 gene, causing recessive dystrophic epidermolysis bullosa. Issue 2 (April 2020) - Rehman, Atta Ur; Peter, Virginie G.; Quinodoz, Mathieu; Dawood, Muhammad; Rivolta, Carlo
Abstract : Dystrophic epidermolysis bullosa is a major form of epidermolysis bullosa and may be inherited as an autosomal dominant or recessive trait, with associated mutations in the COL7A1 gene. Here, we describe a consanguineous Pakistani family with four affected individuals suffering from recessive dystrophic epidermolysis bullosa. Exome sequencing of the proband's DNA revealed a homozygous missense variant (c.8038G>A:p.Gly2680Ser) in COL7A1 which cosegregated with disease in the family. The emergence of this particular glycine substitution in patients from diverse ethnic backgrounds such as China, United Kingdom, Poland, Iran, and Pakistan indicates that this variant most likely constitutes a recurrent mutational hotspot in the COL7A1 gene, rather than a germline mutation present at low levels in the general population.